Embarking on a new academic journey: ROVERX22 guides RX22 through exciting opportunities / Ili Rabiatul Adawiah Ismail, Muhammad 'Izzuddin Zamery and Nik Aisyah Najwa Nik Mustaffa Shapri - Ismail, Ili Rabiatul Adawiah; Zamery, Muhammad 'Izzuddin; Nik Mustaffa Shapri, Nik Aisyah Najwa (Faculty of Pharmacy, 2023)
Starting university is an exciting and transformative experience in a student's life, marking the beginning of a new chapter filled with academic challenges, personal growth, and the opportunity to forge lifelong friendships. To help our new Pharmily make a smooth transition into this pivotal phase of their education, the Society of Pharmacy Students (SOPHYS) organized 'Realizing Opportunities, Vision, Empowerment, and Resilience For RX22' program affectionately known as ROVERX22, which held on the 7th of October 2023 at Dewan Kuliah 500. This event aimed to provide comprehensive academic and extracurricular insights into the Bachelor of Pharmacy (Hons.) program for the RX22 cohort, ensuring that students gain a well-defined understanding of this four-year course. The program commenced with an insightful session by the Dean Faculty of Pharmacy, Prof. Dato' Dr. Abu Bakar Abdul Majeed followed by Deputy Dean of Students' Affairs Dr. Aida Azlina Ali Faculty of Pharmacy, who offered insights into academic preparedness, career prospects, and personal development at Faculty of Pharmacy UiTM. In the afternoon, students had the opportunity to interact with Ms. Izzati, a counselor who offered her insights on the transition to campus life